Nutritional and health status of HIV+ adults stable on HAART attending a healthcare facility in Cape Town, South Africa - Oyetunji, Iyanuoluwa Oyedeji (Department of Human Biology, 2023)
Background: PLWH have twice the chances of developing cardiovascular disease (CVD) when compared to the uninfected population. This and other NCDs are important cause of non-AIDS related mortality among PLWH, and its prevalence may increase as PLWH continue to age. Factors that may have association with the increased risk of NCDS among PLWH have been identified including the use of HAART, systemic inflammation, male gender, aging, diet, and sedentary lifestyle. The relationship between higher diet quality and a lower risk of NCDs has been reported among PLWH. Furthermore, dietary interventions have reduced the risk of NCDs among PLWH. However, studies assessing dietary intake among PLWH in South Africa are not recent and were conducted among ART-naïve participants. This dissertation contains a scoping review of literature that sought to identify the diet quality and food insecurity indices that have been used among PLWH and how these constructs are associated with the risk of developing CVD. The primary study component assessed the nutritional and health status of adults living with HIV stable on HAART attending the Heideveld CHC in Cape Town. We also investigated the association that may exist between these factors, especially diet quality, and the risks of NCDs. Methods: For this thesis, a scoping review and primary study was conducted. For the scoping review, the frameworks of Arksey and O'Malley, the Joanna Briggs Institute's (JBI) manual for conducting scoping reviews, and the Preferred Reporting Items for Systematic review and Meta Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines were used for the scoping review. The protocol was registered on OSF registries and published in BMJ Open. Extracted data were presented in tables, followed by a descriptive summary of findings. A search strategy was developed, and a preliminary MEDLINE (via PubMed) search was conducted followed by a final search on PubMed, EbscoHost, Scopus, Web of Science, and COCHRANE library databases. The findings from the scoping review were also used to refine the protocol of the cross-sectional study. The primary study was descriptive and cross-sectional including 247 adults receiving HAART from the Heideveld CHC. Eligible participants were HIV positive, on HAART for at least 1 year, aged 18 years or older, and able to communicate in English language, isiXhosa, or Afrikaans. Ethical approvals were obtained from the UCT ethics committee and the Department of Health. Data were collected using an interviewer-administered questionnaire and the patients' folder. Data were collected on socio-demographic variables, HIV infection-related information, anthropometry, biochemical, and clinical measures, as well as weight perception, satisfaction, and management goals. Other measures included dietary intake and habits, food security, physical activity, self-esteem, smoking, and alcohol intake. Data were captured using Microsoft Excel (version 2180) and analyzed using RStudio Version 1.2.5033. Appropriate statistical methods were used to summarize and describe the results. Results: A total of 31 studies were included in the scoping review after the recommended multilevel screening against the inclusion criteria. Three studies assessing food security status showed that food insecurity was high in PLWH. Six studies assessing dietary adequacy using a predefined diet quality index showed that PLWH had moderate adherence to the Healthy Eating Index (HEI) and Mediterranean Diet Score (MDS) guidelines. However, adherence to the recommendation of individual food items or nutrients was low. Other studies presented intakes of individual nutrients or food components. Two African studies were included with none using a diet quality index. The two most reported CVD risks were obesity and hypertension. The association between diet and risk of CVD reported was complex; while some studies found significant associations, some did not. In the primary study, the majority (69.9%) were females with a median age of 46 years. The median duration of infection was 12 years, the median ART duration was 10 years, and 94.7% had a suppressed viral load. One-third of the participants had comorbidities, hypertension was the most prevalent comorbidity reported, followed by dyslipidemia and diabetes. Other comorbidities reported were CVD, renal problems, and cancer. The prevalence of obesity was 40.7% while 27.6% were overweight. Based on predefined criteria, 50.0% of the participants had high blood pressure. Food insecurity was reported by 89.0% of the participants. The median intake of fruits and vegetables was 0.9 and 1.6 servings/day respectively. Habitual consumption of SSB and processed meat on average of 1.0 servings/day was reported. Mean (SD) DASH and Alternate Healthy Eating Index (aHEI) scores were 21.6 (5.1) and 41.9 (9.8) respectively. While 80.0% did not try to gain weight in the previous year, 51.0% gained weight. However, 58.0% were happy with their present weight. There were significant differences between the three BMI categories for gender (p< 0.001), level of education (p< 0.001), ever being pregnant (p=0.046), creatinine (p=0.002), systolic BP (p=0.010), relative hand grip strength (p< 0.001), PA (p<0.001), and being a smoker (p< 0.001). There was a significant difference between those who were hypertensive and those who were not for age (p< 0.001), level of education (p=0.019), and ever being pregnant (p=0.008). There was no significant association between aHEI score and BMI, as well as DASH score and hypertension. Conclusions: Findings from the scoping review suggest that the majority of PLWH are affected by food insecurity and achieve only moderate adherence to recommendations for diet quality. Few studies have used diet quality indices to assess dietary adequacy among PLWH, and the association of diet with risks of CVD is complex and needs further research. In our primary study, the prevalence of obesity and hypertension was high among the participants, and hypertension was the most prevalent comorbidity reported. The participants were mostly middle-aged females, they were on long-term ART and most of them had an undetectable viral load. The dietary habits and consumption of participants did not conform to recommendations. Obesity was more likely among females, those who had completed high school education, women who had been previously pregnant, those who were sedentary, and less likely among those who were previous and current smokers. Hypertension had a significant positive association with age. Diet quality was not significantly different among PLWH with or without comorbidities. The findings of this study emphasize the need to incorporate holistic nutrition education into HIV care at the PHC level. More nutrition-focused research is needed among PLWH in South Africa.